EVALUASI PELAKSANAAN PROGRAM DESA MANDIRI BENIH (PDMB) DI KABUPATEN ROKAN HULU TAHUN 2015-2017 - Andriani, Siska; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Seed Independent Village Program (PDMB) is a follow-up to the Indonesian president Joko Widodo's program in realizing food independence, the effort of the collar is to increase productivity by increasing the quality of the seeds used. The aim is to increase capacity to meet the needs of seeds in their respective regions. The purpose of this research is firstly how to Evaluate the Implementation of the Independent Seed Village Program in Rokan Hulu Regency 2015-2017. Secondly, to find out the factors that hinder the evaluation of the implementation of the Seed Independent Village Program in Rokan Hulu Regency. The theoretical concept used by the author is the Public Policy Evaluation Criteria in the implementation of the program by William N. Dunn. This research uses qualitative research methods with descriptive studies.             The results of this study indicate that the evaluation of the implementation of the Independent Seed Village Program (PDMB) in Rokan Hulu Regency from the six indicators of the policy evaluation criteria used is effectiveness, there are still a number of villages where the PDMB has not succeeded in achieving the target program. Efficiency, the amount of effort done by program implementing actors by providing assistance and providing counseling, training or guidance. Adequacy, the funds provided in the implementation of the program depend on the use or utilization of each PDMB and some villages feel they are sufficient on the funds provided. Flattening, this program is given evenly to the people whose villages are categorized as seed prone. Responsiveness, the response of the community is not good because community complaints are not responded to be followed up. And accuracy, this program since 2015 is still used as the right solution to increase seed production, especially in their respective regions. Several factors hampered the evaluation of program implementation such as lack of human resources in program implementation, local regulations regarding the program, lack of government handling of unstable weather conditions and lack of socialization by related actors in program implementation. Keywords: Policy Evaluation, Food, Seed Independent Village Program.